Pengaruh Manajemen Laba Pada Nilai Perusahaan Dengan Agresivitas Pajak Sebagai Variabel Intervening - Wahyuni, Ni Wayan Intan Saskara; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 29 No 3 (2019)DO - 10.24843/EJA.2019.v29.i03.p11, 2019)
This study aims to analyze and determine the effect of earnings management on company value with tax aggressiveness as an intervening variable. The theoretical implications of this research to be able to support the application of agency theory and signaling theory by conducting research on a straightforward basis. The study was conducted on mining companies listed on the Indonesia Stock Exchange in 2012-2018. This study uses quantitative data types and secondary data sources with the number of observations obtained as many as 60 observations determined using the nonprobability sampling method with a purposive sampling technique as a sample selection method. Data analysis technique used in this research is path analysis with SPSS program. Based on the results of the path analysis in this study shows that earnings management has no effect on tax aggressiveness. Tax aggressiveness has a negative effect on company value. Earnings management has a negative effect on company value. Earnings management does not affect indirectly the value of the company through tax aggressiveness. Keywords : Earnings Management; Tax Aggressiveness; Company Value.